Synthesis of enantiopure sugar-decorated six-armed triptycene derivatives - Bonaccorsi, Paola; Gioia, Maria Luisa Di; Leggio, Antonella; Minuti, Lucio; Papalia, Teresa; Siciliano, Carlo; Temperini, Andrea; Barattucci, Anna (Beilstein Journal of Organic Chemistry, 2013)
A new class of molecules with a triptycene rigid core surrounded by six monosaccharide residues was synthesized. Hexakis(bromomethyl) substituted triptycene was converted into a six-armed triptycene azide (2,3,6,7,14,15-hexakis(azidomethyl)-9,10-dihydro-9,10-[1’,2’]benzenoanthracene). The key step of the synthesis was the cycloaddition of the azide to 2-propyn-1-yl β-D-gluco- or galactopyranosides. All products were isolated in good yields and were fully characterized.
Keywords: azide derivatives; click chemistry; glycoconjugates; 2-propyn-1-yl β-D-glycopyranosides; triptycene